Hepatoprotective and nephroprotective activities of Juniperus sabina L. aerial parts - Maged S. Abdel-Kader; Mubarak T. Alanazi; Abdulaziz S. Bin Saeedan; Fahad I. Al-Saikhan; Abubaker M. Hamad (GarVal Editorial Ltda., 2017)
Context: Previous studies indicated that Juniperus species exhibited promising hepatoprotective activity. Aims: To evaluate the hepatoprotective and nephroprotective activity of the total alcohol extract of the aerial parts of Juniperus sabina against carbon tetrachloride (CCl4) induced toxicity using male Wistar rats as experimental animals. Methods: Daily oral administration of two doses (200 and 400 mg/kg) of the total extract of the aerial parts of J. sabina for seven days followed by one dose of CCl4 (1.25 mL/kg) at day 6. Liver and kidney functions were monitored via measuring serum and tissue parameters as well as histopathological study. Normal rats, rats treated only with CCl4 and rats treated with CCl4 and silymarin were used as controls. Results: The higher dose showed 47, 50, 38, 17 and 42% decrease in the levels of AST, ALT, GGT, ALP, and bilirubin respectively. Animals received the total extract of J. sabina showed a significant dose-dependent recovery of the NP-SH contents, total proteins, and reduction the level of MDA in both liver and kidney tissues. Histopathological study revealed improvement in the architecture of hepatocytes and kidney cells. Conclusions: The hepatoprotective effect offered by J. sabina crude extract at the two used doses was found to be significant in all serum parameters. Histopathological study revealed moderate improvement in the architecture of the liver cells that add another indication of protection. Improvement of kidney function was less than liver function.